Optical coherence tomography angiography biomarkers of microvascular alterations in RVCL-S - Al-Nofal, Mays; de Boer, Irene; Agirman, Seda; Wilms, Anne E.; Zamanipoor Najafabadi, Amir H.; Terwindt, Gisela M.; Notting, Irene C. (Frontiers in Neurology, 2022)
Background: The brain and retina share many neuronal and vasculature characteristics. We investigated the retinal microvasculature in patients with a monogenic vasculopathy using optical coherence tomography angiography (OCTA). OCT-A is a novel precise noninvasive imaging method that may provide biomarkers suitable for diagnosis and follow-up of small vessel diseases. Methods: In this exploratory cross-sectional study, eleven RVCL-S patients and eleven age-matched healthy control participants were included. The size of the foveal avascular zone (FAZ) and the vascular density of the superficial capillary networks in the retina were measured by OCT-A. Results: The symptomatic and presymptomatic patients showed significantly lower vascular density values than controls in the foveal region (median [IQR] 18.2% [15.8 – 18.6] vs. 24.4% [21.5 – 26.8] (p < 0.001), 29.8% [29.6 – 30.8] vs. 33.2% [32.0 – 33.6] (p = 0.002), respectively). The FAZ was significantly larger in the symptomatic RVCL-S patients than in the control group [13416 square pixels [7529 – 22860] vs. 1405 square pixels [1344 – 2470] (p < 0.001)). No significant difference was identified in measurements of FAZ comparing presymptomatic and controls. Conclusion: Our findings with OCT-A demonstrated that RVCL-S causes an increase in the size of the FAZ in symptomatic RVCL-S patients compared to healthy participants. Moreover, there is a decrease in vessel density in the superficial capillary networks in both symptomatic and presymptomatic patients. In the future, newly developed precise objective instruments such as OCT(-A) may provide important tools in determining disease activity for follow up of common small vessel diseases.